A novel method for the synthesis of symmetrical triacylglycerols by enzymatic transesterification. (November 2015) - Tang, Wenjia; Wang, Xiaosan; Huang, Jianhua; Jin, Qingzhe; Wang, Xingguo
Highlights: Symmetrical triacylglycerols (STAGs) had been synthesized by transesterification. Enzymatic transesterification for STAGs synthesis is a greener route. Enzymatic reaction using fatty acid vinyl ester as acyl donor is irreversible. Low acyl migration rate during transesterification were due to the irreversibility. Abstract: A novel two-step enzymatic method is described in this study to synthesize symmetrical triacylglycerols (TAGs) with arachidonic acid (ARA) at the sn -2 position. The processes included the synthesis of 2-monoacylglycerols (2-MAGs) rich in 2-arachidonoylglycerol (2-AG) by enzymatic ethanolysis and the synthesis of symmetrical TAGs by enzymatic transesterification between 2-MAGs and vinyl palmitate. Under the optimal conditions, desired symmetrical TAGs were obtained at 89% yield. In this study, vinyl palmitate rather than palmitic acid was used as a novel acyl donor to react with 2-MAGs. It was the first study reporting the synthesis of symmetrical TAGs by enzymatic transesterification. The reaction using fatty acid vinyl ester as acyl donor is irreversible and temperature is low. Low-temperature reaction greatly suppressed the acyl migration of 2-MAGs and the irreversible reaction is much more effective compared to reversible reactions using free fatty acid and fatty acid ester as acyl donors.